All Days 1994
DOI: 10.2118/28826-ms
|View full text |Cite
|
Sign up to set email alerts
|

Relative Permeability Measurements: An Inter-Laboratory Comparison

Abstract: CwWht <994 Sode!y o! Pev@uti EM,ws. 10C, This PW w mewed for me,mlatlm a! the Eurawa" Pf.tmla"mI Cmkrw.cd held f" London. U.K., 25'27 OCtcbW 4SW TM, $aPs, w Mmled "brPra,mta,tm by m SPE PIowm COtiiitle. fdbwlw rwkw 'of I"bml.sib) can!almd 1" ." aMlacI s@mlU6d by ?h. ati.r(,]. C0n,en18 01 ,~eP9!xr, asPrmmt,d, have not be" revlewd by lb SmlW 01 Pe!m[,um Englnmrs and W. sub]ea toc."atilm W W w4w?(s). T@ rmt.rhi asPms4"td, 60,$ not rwmnrtly reflect w with. d w Scciew.1 Petroleum Fniahmr., lbNice% wmmimrs. WOBPrese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In most of the documented cases the endpoint relative permeabilities 1.4 < k r < 2.4 (McPhee 1994;McPhee and Arthur 1994). These cases have in common that the (near) endpoint relative permeabilities k r > 1 in particular, when the non-wetting phase is the majority phase (McPhee 1994;McPhee and Arthur 1994;Karabakal and Bagci 2004) and the wetting phase is present only as thin wetting films covering the rock surface. In oil-wet systems (wetting-index −1) the k r,w (S o,r ) > 1 and in water-wet systems k r,o (S w,c ) > 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the documented cases the endpoint relative permeabilities 1.4 < k r < 2.4 (McPhee 1994;McPhee and Arthur 1994). These cases have in common that the (near) endpoint relative permeabilities k r > 1 in particular, when the non-wetting phase is the majority phase (McPhee 1994;McPhee and Arthur 1994;Karabakal and Bagci 2004) and the wetting phase is present only as thin wetting films covering the rock surface. In oil-wet systems (wetting-index −1) the k r,w (S o,r ) > 1 and in water-wet systems k r,o (S w,c ) > 1.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually assumed that the relative permeabilities 0 ≤ k r ≤ 1. However, there are several reports in the literature that explicitly show endpoint relative permeabilities k r > 1 (Odeh 1959;Dullien 1992;Anderson 1987;McPhee 1994;McPhee and Arthur 1994;Karabakal and Bagci 2004;Honarpour et al 2000;Arps and Roberts 1995;Ehrlich 1993;Mikkelsen and Scheie 1991). The term "endpoint" refers to the relative permeability at the saturation endpoints, S w,c and S o,r .…”
Section: Introductionmentioning
confidence: 99%
“…In 1959, using core plugs from consolidated rock, Odeh (52) observed effective permeabilities to oil at initial water saturation which were up to 2.4 times the permeabilities to brine totally saturating the core plug. More recently, McPhee & Arthur (53) observed a similar phenomenon with core plugs of consolidated Clashach sandstone.…”
Section: Two Phase Flowmentioning
confidence: 67%
“…McPhee & Arthur (53) explored "bump floods" at the end of a relative permeability test, where the flow rate of water through a core plug was increased by a factor of 100 at the end of an oil displacement test. They found that the higher velocity flow of water increased the displacement of oil only slightly, but increased the effective permeability to water by a factor almost of 4.…”
Section: Two Phase Flowmentioning
confidence: 99%
“…The combination of low aspect ratio and moderate to high contact angles make relative permeabilities for these cores largely insensitive to displacement rate. McPhee and Arthur [30] report a comparative study of four service laboratories using similar methods and cores. The overall trend is for relative permeabilities to increase and residual saturations to decrease with increasing displacement rate.…”
Section: Network Model Predictions For Berea Relative Permeability Datamentioning
confidence: 99%